A qualitative study on the clinical safety and user experiences of female condoms for anal intercourse among men who have sex with men in Shanghai, China - Jia-Lu Huang; Xin Xin; Xin Xin; Xin Xin; Ming-Jun Ma; Zhen Ning; Shao-tan Xiao; Shao-tan Xiao; Pan-pan Chen; Pan-pan Chen; Pan-pan Chen (Frontiers in Public Health, 2023)
ObjectiveThis qualitative study aimed to understand the clinical safety, efficacy, and receptiveness of using the female condom (FC) during anal intercourse among men who have sex with men (MSM).MethodsSubjects for this study were recruited from a two-group crossover trial among MSM in Shanghai. The trial consisted of two phases, each including the use of condoms (FC vs. male condom), questionnaires, and in-depth one-on-one interviews. The two phases were separated by a washout period of 4 weeks. The minimum sample size for this study was determined in accordance with the principle of “information saturation.” The qualitative data were organized and analyzed using ATLAS.ti version 7.ResultsA total of 26 participants from the MSM population were recruited for this study, with 10 assuming the insertive role (i.e., “1”), 8 assuming the receptive role (i.e., “0”), and 8 being versatile (i.e., “0.5”). Each participant completed the crossover trial comprising two phases. The cumulative usage of FCs and male condoms (MCs) amounted to 115 and 127 times, respectively. During the reported sexual encounters, no participants reported incidents of condom rupture, slippage, or other malfunctions. A few participants reported experiencing slight chafing pain, primarily put forward by “0” participants. Apart from those reports, no instances of bleeding, swelling, or allergic reactions were reported. The efficiency of FC in disease prevention, the sexual partner’s willingness to use FC, the freshness of FC, and positive sexual experiences were the main reasons for the consistent use of FC for anal sex. Discomfort and pain during sexual activity, the loose design and thick material of FCs, and difficulties in placing FCs were the major obstacles to FC use among MSM. The elements referring to the forehead exhibited varied in importance among “1,”, “0,” and “0.5” participants. Regarding the willingness to use the FC in the future anal intercourse, 61.54% of participants expressed a positive inclination, 23.08% were uncertain, and 15.38% stated that they would not. “A better sense of security during anal sex” was the main factor affecting willingness among “0” participants and “the sexual pleasure that the FC brought” among “1” participants. Improving the design and technology of FCs and increasing the frequency of use and practice might improve the use skills, which will favor the willingness to use FCs among the MSM population.ConclusionFCs received positive user feedback from study participants, but distinctions were found in individuals in different sexual roles. Large-scale quantitative studies are needed to evaluate the clinical safety of the FC and its effectiveness in preventing the transmission of STDs during anal intercourse.